LEVELS OF INTERLEUKINS AND MELATONIN IN PATIENTS WITH ACUTE CORONARY SYNDROME - M. A. Shalenkova; Z. D. Mikhailova; E. T. Manukova; T. A. Basalgina; A. P. Shishkina (Медицинская иммунология)
The issues of cytokine activation in patients with ischemic heart disease (IHD) are widely discussed in medical literature, including both chronic and acute clinical course of the disorder. However, appropriate changes still remain unclear. E.g., attention in research is drawn to possible role of melatonin (MT), an epiphysis hormone. The available findings on MT production in acute forms of IHD are controversial. We have determined blood levels of IL-6 and IL-10 in 98 patients with IHD, of them 93 suffering from acute coronary syndrome (ACS), and 5, with stable angina pectoris (SAP), functional class II-III, and evaluated their correlation with urinary contents of the MT metabolite (6–hydroxymelatonin, 6-HOMT). ACS patients, when compared with SAP patients, showed an increase of IL-6 and IL-10 levels, whereas 6-HOMT contents were found to be decreased. In the patients with unstable angina pectoris and non-Q myocardial infarction (IM), we have revealed more elevated values of IL-6 and IL-10, as well as 6-HOMT. IL-6 and IL-10 levels appeared to be higher and those of 6-HOMT proved to be lower in patients with a history of anterior IM. The levels of 6-HOMT were found to be significantly increased in the patients with complicated IM. The levels of IL-6 and IL-10 in blood and 6-HOMT in urine can be used as auxiliary diagnostic criteria, in order to predict possible development of cardiovascular complications during ACS during hospital period.